2015
DOI: 10.15252/embj.201490693
|View full text |Cite
|
Sign up to set email alerts
|

JNK ‐dependent gene regulatory circuitry governs mesenchymal fate

Abstract: The epithelial to mesenchymal transition (EMT) is a biological process in which cells lose cell–cell contacts and become motile. EMT is used during development, for example, in triggering neural crest migration, and in cancer metastasis. Despite progress, the dynamics of JNK signaling, its role in genomewide transcriptional reprogramming, and involved downstream effectors during EMT remain largely unknown. Here, we show that JNK is not required for initiation, but progression of phenotypic changes associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 69 publications
2
27
0
Order By: Relevance
“…Therefore, we next questioned whether classical migration genes involved in epithelial–mesenchymal transition (EMT) are induced following NeuroD1 expression. To address this question, we compared the NeuroD1‐induced genes with genes that we recently identified as upregulated during EMT (Sahu et al , ). Interestingly, this analysis showed that URG encompass a large number of genes that are upregulated during EMT ( n = 878, ~40%) and include a number of hallmark genes that are known to promote EMT (Fig L).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we next questioned whether classical migration genes involved in epithelial–mesenchymal transition (EMT) are induced following NeuroD1 expression. To address this question, we compared the NeuroD1‐induced genes with genes that we recently identified as upregulated during EMT (Sahu et al , ). Interestingly, this analysis showed that URG encompass a large number of genes that are upregulated during EMT ( n = 878, ~40%) and include a number of hallmark genes that are known to promote EMT (Fig L).…”
Section: Resultsmentioning
confidence: 99%
“…The strongly downregulated HMGB1 has been shown to be downregulated in adult neurons (Guazzi et al, 2003). Interestingly enough, also the transcription factor TSC22D1, which was very recently linked to JNK-dependent (neuronal) differentiation processes (Sahu et al, 2015), is upregulated. From a mechanotransductive point of view also the upregulation of LAP2 (lamina-associated polypeptide 2) is quite interesting, as it is involved in the organization of the nuclear and chromatin structure, and the nucleoplasmic transport of lamin A (Dechat et al, 1998; Osmanagic-Myers et al, 2015), a protein recently found to be essential in mechanotransductive signaling (Swift et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the activation of MAPK-JNK pathway was closely associated with lung tumorigenesis (39,40). JNK not only could regulate critical EMT genes through inducing key transcription factors to influence the progression of phenotypic changes but also regulated MMPs (such as MMP-1, MMP-2, and MMP-9), which played important roles in cell outgrowth, tissue destruction, and inflammation (27,(41)(42)(43). However, the detail regulatory mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…RCC2 activated JNK pathway to induce EMT and extracellular matrix remodeling of LUAD cells JNK pathway is critical for the progression and maintenance of phenotypic and cellular changes associated with EMT (27).…”
Section: Rcc2 Promoted Xenograft Tumor Growth and Metastatic Potentiamentioning
confidence: 99%